Sistem Informasi Pengelolaan E-Billing Warga di Lingkungan RW 001 Kelurahan Rawajati Kecamatan Pancoran dengan menggunakan Framework CodeIgniter - Dwi Juliastuti; Agung Triayudi; Eri Mardiani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
For the formation of prosperous citizens, it is necessary to have good management in service to residents, one of which is the financial management of the Rukun Warga (RW) which contains community contributions for payment along with income and financial expenditure reports. This problem is currently being faced by residents and treasurers in the RW environment. 001 Rawajati Subdistrict, Pancoran Subdistrict, it is difficult to find data and payment reports that are not neatly arranged considering the large number of residents who make payments every day because the payment process is still very simple and you cannot see anything. It's just that fees that have been paid or those that haven't been paid, especially during this pandemic, people prefer to use digital transactions compared to manual or using cash. The benefits of this research, in the research methodology that will be carried out using methods of literature study, interviews, and observation. The author designs and builds a website-based accounting information system and the Codeigniter framework that involves 2 system users, namely residents and treasurer. Residents can view bills, make contribution payments, view the history of bills that have been or have not been paid, and reports on financial expenditures, namely the treasurer as a user who is currently inputting citizen data, citizen contribution billing data, and inputting financial expenditure reports. The results of this study can handle the entire process of recording administrative transactions from incoming fees incurred to preparing transaction reports to obtain more accurate information. The test results use the System Usability Scale (SUS) method with an average SUS score of 77.9 and it is certain that the respondents agree with the application of management accounting in RW 001